Unveiling the hidden robber-fly diversity: Merucata, a new Neotropical Asilinae genus (Diptera, Asilidae) with description of seven new species - Soares, Matheus M.m.; Camargo, Alexssandro; Scorpione, Gabriela; Lamas, Carlos J.e. (Zootaxa, 2025)
Merucata gen. nov. is erected to include the following seven new species that are herein described and illustrated from Brazil: Merucata caipora sp. nov., M. capixaba sp. nov., M. cerradensis sp. nov., M. contiae sp. nov., M. curupira sp. nov., M. pujoli sp. nov., and M. vieirai sp. nov. In addition, Merucata elliptica (Scarbrough & Perez-Gelabert, 2010) comb. nov. described from Trinidad and Tobago is transferred from Martintella Artigas, and newly recorded from Venezuela. The new genus is placed into the Myaptex group of the subfamily Asilinae based on the following set of characters: wing with cells r2+3 and r4 not separated by a recurrent vein (i.e., only two submarginal cells), vein R5 ending after wing apex, scutellum tumid, with no sign of an impressed rim and with at least one pair of well-developed marginal scutellar macrosetae, claws acute, and abdominal tergites with lateral marginal macrosetae. Merucata gen. nov. can be differentiated from the other genera of the group by the scutum lacking anterior dorsocentral setae, abdominal sternites lacking macrosetae, male epandrium with inner medial dorsal process covered with short and dense macrosetae, and phallus with three long prongs, encompassing about half of the phallus length. An updated key to the genera of the Myaptex group along with an illustrated identification key to the males of the species of Merucata gen. nov. and distribution maps are also provided.